High microbial translocation limits gut immune recovery during short-term HAART in the area with high prevalence of foodborne infection - Doungnapa Kantamala (2020)
© 2020 Elsevier Ltd Background: Individuals residing in areas with high prevalence of foodborne infection could have a higher risk of gut microbial translocation which may affect monocyte activation, gut immune recovery and intestinal epithelial cell damage. We aimed to measure alterations in microbial translocation, monocyte activation, gut immune recovery, and intestinal epithelial cell damage in HAART treated individuals. Methods: A prospective, single-arm, longitudinal, cohort study was conducted among antiretroviral naïve HIV-1 infected Thai participants. All participants were in chronic stage of HIV-1 infection before starting HAART. Data and samples were collected prior to initiation of HAART and then after 24 and 48 weeks of HAART. Plasma biomarkers for microbial translocation (16S rDNA and LBP), monocyte activation (sCD14) and intestinal epithelial cell damage (I-FABP) were evaluated. We measured circulating gut-homing CD4+ T cells and circulating gut-homing Th17 cells to assess recoveries of gut immunity and gut immunity to microbial pathogens. Results: The kinetic studies showed no reduction in the levels of plasma 16S rDNA, sCD14 or I-FABP, significant decrease of plasma LBP level, and slow but significant increases in the frequencies of circulating gut-homing CD4+ T cells and circulating gut-homing Th17 cells during 48 weeks of HAART. Dividing participants into low and high microbial translocation (low and high MT) groups at baseline, both groups showed persistent plasma levels of 16S rDNA, sCD14 and I-FABP, and significantly decreased plasma level of LBP. The low MT group had significantly increased frequencies of circulating gut-homing CD4+ T cells and circulating gut-homing Th17 cells during 48 weeks of HAART but this was not observed in the high MT group. Conclusions: We demonstrated persistent high microbial translocation, monocyte activation and intestinal epithelial cell damage with slow gut immune recovery during successful short-term HAART. Additionally, gut immune recovery was apparently limited by high microbial translocation. Our findings emphasize the adverse impact of high microbial translocation on gut immune recovery and the necessity of establishing a novel therapeutic intervention to inhibit microbial translocation.